(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the nutritional status of hospitalized patients with pneumonia. Subjects and methods: A cross-sectional study was conducted on 150 inpatients diagnosed with pneumonia at Thieu Hoa General Hospital from August 2024 to March 2025. Collected data included demographic characteristics and anthropometric measurements. Nutritional status was assessed using BMI and the SGA too. Results: According to BMI, 15.3% of patients were classified as malnourished. Based on the SGA, 58% of patients were identified as being at risk of malnutrition. Conclusion: The prevalence of malnutrition and the risk thereof remain high among hospitalized patients with pneumonia. Early detection and timely nutritional intervention are essential to enhance treatment outcomes and recovery during hospitalization.